ANALISIS PENGARUH ALIH FUNGSI LAHAN PERTANIAN TERHADAP KETAHANAN PANGAN DI KECAMATAN BAYAN KABUPATEN PURWOREJO TAHUN 2013 DAN TAHUN 2023 - Mahmudah, Fitri Tri; Sarwono; Utomowati, Rahning (Indonesian Journal of Environment and Disaster, 2024)
The objectives of this study are (1) To analyze agricultural land conversion the Bayan District in 2013 and 2023. (2) To analyze food security the Bayan District in 2013 and 2022. (3) To analyzing the impact of agricultural land conversion on food security the Bayan District. This research employs a quantitative descriptive method with a spatial approach. Data collection methods involved observation, documentation, and image interpretation. Data analysis techniques used map overlay analysis, calculation of food availability ratio, and paried sample t-test statistical test. The results of this study show that: (1) The conversion of agricultural land (paddy field and moor) the Bayan District in the period 2013 - 2023 is 78.37 hectares (3.11%). (2) Food security the Bayan District in the period 2013 – 2022 averall shows a food surplus condition, this can be seen from the value of food availability ratio that exceeds 1 in each village/sub-district. However, there are 2 villages in 2022 that experience food deficit, these areas are Grantung Village and Pekutan Village. (3) The effect of agricultural land conversion on food security the Bayan District is known from the results of the paired sample t-test statistical test with a Sig value of 0.317, the value is greater than the alpha value of 0.05, therefore, H0 is accepted and H1 is rejected. So it can be concluded that there is no significant effect of agricultural land conversion on food security the Bayan District.